A review of pregnancy outcomes in obese mothers and compliance with local standards for antenatal and postpartum care. (16th November 2010) - Rao, U; Finney, V; McCormack, J
Abstract : Introduction: Obesity is now a major public health issue with 24% of adults in England with a body mass index (BMI) of 30 or greater. This has obvious major implications for pregnancy, maternal health and also effects on the fetus. In the last CEMACH report more than half the women who died from direct and indirect deaths where the information was available were overweight or obese. Patients and Methods: This was a retrospective audit of all pregnant women who delivered in 2009 with a booking BMI of >40. Local protocols include a modified glucose tolerance test for patients with a BMI over 30, serial growth scans with BMI's over 35 and thromboprophylaxis. 25 patients with a booking BMI >40 were included in this audit. Results: Three patients had an early spontaneous abortion. Only three patients were referred to the anaesthetist antenatally. Most patients had a modified glucose tolerance test (GTT) and growth scans. One patient had intrauterine death and 15 patients had vaginal delivery, of which three were preterm. Seven patients had caesarean section's (CS) of which three underwent emergency CS as they failed to progress in the first stage of labour. Postnatally only 12 patients received recommended thromboprophylaxis. Conclusion: This review has shown that local protocols are not being fully followed particularly with regard to thromboprophylaxis. This is obviously an area that needs attention. Some of the data gathered agrees with previously published data however caution should be used in drawing conclusions due to the small numbers involved and gathering more data prospectively would help to affirm any significant trends.